Influence of Lauric Acid Supplementation on Blood Parameters and Antioxidant Activity in Large White Yorkshire Cross Piglets - G.G.Marsha, M.Venkateswarlu; G.Alexander, M.Hanumanth Rao; B.Ekambaram, S.Parashuramulu (Indian Journal of Animal Nutrition, 2024)
To study the influence of lauric acid (LA) supplementation on blood biochemistry and oxidative stress in Large White Yorkshire cross (LWY) piglets, selected 28 piglets (70-75 days age) and experimented for a period of 97 days by randomly allotting to 4 dietary treatments. Basal diet was (BD) prepared without supplementation and an antibiotic (chlortetracycline at 0.05%) supplemented diet (BDA) was prepared as a positive control. The remaining two diets were prepared by supplementing LA at two levels 0.2% (BDL-0.2) and 0.4% (BDL-0.4) to the basal diet. Blood biochemical parameters revealed that the total protein, albumin, globulin and total cholesterol levels were significantly affected with lauric acid supplementation, while glucose, blood urea nitrogen (BUN) and ratio of albumin:globulin were not affected by LA and antibiotic. The antibiotic and LA supplemented piglets had higher (P<0.05) total protein values, while lowest (P<0.05) values recorded in BD group. Significantly higher serum albumin and globulin levels were recorded in piglets fed BDL-0.4 and was comparable to BDL-0.2 and BDA groups, with the lowest (P<0.05) values in BD group. The total cholesterol and lipid peroxidase (measure of oxidative stress) were highest (P<0.01) in BD fed group, while significantly reduced in LA and antibiotic supplemented groups. The higher (P<0.01) activity of Glutathione peroxidase was observed with LA supplementation, while Catalase values did not differ between groups. Therefore, it was concluded that LA supplementation in LWY piglets decreased the total cholesterol and increased the total protein, albumin and globulin contents in the blood with no effect on glucose and BUN contents. Further, reduced the oxidative stress by enhancing antioxidant enzyme activity and minimized the lipid peroxidation. Thus it is an imperative that lauric acid could be an alternative to antibiotics usage in piggery farming.